Where's the money in big data - Guleri, Tim.; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa Clara, Calif.) ([United States?] : O'Reilly Media, 2011)
"The ability to collect, crunch, act upon, and share huge amounts of data disrupts nearly every industry, tearing down barriers to entry and creating entirely new businesses." --Resource description page.
Title from title screen.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, Calif.
Electronic reproduction.
Keywords: Business intelligence -- Data processing; Electronic data processing; Electronic books